CHARACTERIZATION AND INCORPORATION OF THE MILK ACTIVITY IN THE ALTA PAULISTA REGION - OLIVEIRA, Sandra Cristina de; PINTO, Leonardo de Barros; PIGATTO, Gessuir; SIMON, Elias José (Revista Brasileira de Engenharia de Biossistemas, 2010)
The milk activity has always been present in the region Alta Paulista and it plays a pivotal role in generating employment and income. This activity experienced changes in the 1990s that took place nationwide, and brought changes in their mode of production and market insertion. This work aims to characterize the milk activity in Alta Paulista region, as well as how to insert of the different agents involved in it. Semi-structured questionnaires were applied to firms and producers listed by institutional actors in the region. It was observed that collective action appears as a key strategy to minimizing the problems faced by the production sector, since the dynamics of the market has been acting towards selecting dairy farmers for production scale, quality of raw material and professionalism in business management. Companies interviewed have lack of monitoring of manpower, strategic planning, information technology and investment in marketing programs. The lack of knowledge about the benefits (or existence) of some management tools can justify such results, and seriously undermine the competitiveness of the company. However, the solution is under direct control of the company. Such initiatives show themselves as alternatives to a better integration of production and the dairy industry in the market